Oral treatment options for patients with urinary tract infections caused by carbapenem-resistant Escherichia coli - Malik, Nasrullah; Sultan, Aqib; Nizamuddin, Summiya; Shameem, Farah (Infectious Diseases Journal of Pakistan, 2024)
Background: Urinary tract infections (UTIs) are prevalent globally, with Escherichia coli being the predominant pathogen. Carbapenem-resistant E. coli strains exacerbate the clinical burden due to restricted treatment options. This study assessed the antibiotic susceptibility profiles of carbapenem-resistant E. coli strains associated with UTIs, aiming to identify effective oral treatment alternatives. Material and Methods: The Cross-sectional study was conducted in the section of microbiology of the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, from January 2018 to December 2022. This study was undertaken to assess the prevalence of carbapenem-resistant E. coli in urine samples and their susceptibility profiles against fosfomycin, nitrofurantoin, co-trimoxazole, ciprofloxacin, and tetracycline. Results: A total of 978 carbapenem-resistant E. coli isolates were identified during this time period. Approximately 54% (527) of these isolates were recovered from female patients. Fosfomycin, nitrofurantoin, tetracycline, cotrimoxazole and ciprofloxacin were found to be susceptible against 82%, 67.2%, 15.2%, 9.7% and 0.1% carbapenem-resistant E. coli isolates, respectively. More than 80% of all E. coli were sensitive to fosfomycin. Ciprofloxacin exhibited the lowest susceptibility rate. 82% of carbapenem-resistant E. coli isolates were susceptible to fosfomycin, 67.2% to nitrofurantoin, 15.2% to tetracycline, 9.7% to cotrimoxazole, and 0.1% to ciprofloxacin. Conclusion: The emerging carbapenem resistance among gram-negative bacteria markedly limits oral therapeutic alternatives. However, this study displays high susceptibility rates to fosfomycin and nitrofurantoin. We propose their utilization for managing uncomplicated UTIs caused by carbapenem-resistant E. coli. Keywords: Carbapenem resistance, Escherichia coli, Urinary tract infections